2013
DOI: 10.1152/ajpendo.00133.2013
|View full text |Cite
|
Sign up to set email alerts
|

Metformin prevents liver tumorigenesis induced by high-fat diet in C57Bl/6 mice

Abstract: Metformin prevents liver tumorigenesis induced by high-fat diet in C57Bl/6 mice. Am J Physiol Endocrinol Metab 305: E987-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 46 publications
4
54
0
Order By: Relevance
“…Of note, Tajima et al found that metformin decreased HCC incidence when administered concurrently with high fat diet for 60 weeks; however, metformin failed to protect against liver tumorigenesis if treatment was delayed until week 30. 33 While the efficacy of metformin is probably dependent upon both the amount of underlying disease present at the time of treatment in addition to the duration of treatment, our study definitely provides further evidence that early and long-term treatment with metformin is a promising strategy in the prevention of tumors within the liver, its main site of action. 34 …”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Of note, Tajima et al found that metformin decreased HCC incidence when administered concurrently with high fat diet for 60 weeks; however, metformin failed to protect against liver tumorigenesis if treatment was delayed until week 30. 33 While the efficacy of metformin is probably dependent upon both the amount of underlying disease present at the time of treatment in addition to the duration of treatment, our study definitely provides further evidence that early and long-term treatment with metformin is a promising strategy in the prevention of tumors within the liver, its main site of action. 34 …”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, metformin also did not change levels of lipogenioc genes, including SREBP-1c, in a high fat diet model of non-alcoholic fatty liver disease. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Mice were administered metformin, 250 mg/kg/day in PBS (n=10 mice), or PBS alone (n=7 mice) as vehicle control via oral gavage. The metformin dose was selected based on published rodent modeling system precedents 19 , comparable to dosing required for insulin-resistant (type 2) diabetes management in humans (up to 35 mg/kg/day) as determined by allometric scaling 20 . Metformin therapy was initiated 3 days prior to, and terminated 14 days following, PPE infusion.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, studies using carcinogen-induced pancreas, oral, liver, skin, and prostate cancer rodent model systems showed much more profound suppression of tumor formation, which was associated with mTOR inhibition in some cases but independent of AMPK activation in other instances 39-44 . It should be noted that in the case of high-fat diet induced liver carcinogenesis, metformin treatment was effective during the early stages only, not by the time mice developed non-alcoholic fatty liver disease 43 . Of note, the positive studies in pancreas, liver, and skin model systems were performed under high-fat conditions, which may have optimized the opportunities for metformin efficacy.…”
Section: Animal Carcinogenesis Studiesmentioning
confidence: 99%